Theoretically thermal-varying models of the neutral axis position for local damage detection of bridge girders. (15th March 2023) - Wu, Guang-Ming; Li, Sheng-Li; Yi, Ting-Hua; Mei, Xiu-Dao; Wang, Ya-Fei
Highlights: Changes in the centroid of the cross-section stiffness of girders due to temperature gradient. Theoretically thermal-varying model of the neutral axis position for the conventional and composite girders. The neutral axis position is affected by the vertical temperature gradient and the average temperature. Influencing factors include girder height and thermal coefficient of elastic modulus. A theoretical law to eliminate the temperature-induced uncertainty. Abstract: The neutral axis position is sensitive to changes in the cross-sectional area and stiffness of bridge girders but is inevitably influenced by the temperature effect. In the present study, simplified theoretical models between the neutral axis position and the structural temperature were established for both conventional girders and composite girders by introducing the relationship between the elastic modulus and the temperature. The theoretical results of four girders with specified section parameters were then validated by the model girders with different vertical temperature gradients and thermal coefficients of the elastic modulus. The results indicate that the neutral axis position is influenced by the vertical temperature gradient, weighted-average temperature, thermal coefficients of the elastic modulus, and girder height. The relationship between the neutral axis position and the weighted-average temperature of the composite girder is different from that of the conventional girder when the vertical temperature gradient is zero and negative. In addition, the amounts of the thermal-induced variation in the neutral axis position cannot be disregarded in view of the detection of minor damage to the main girder of bridges.